Kajian Hadis mengenai Masjid Ramah Perkembangan Anak - Wakhid Hasyim (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2018)
In Islam, salat becomes one of the rituals that must be done by every individual. To be able to carry out continuously, discipline lead individuals. Ideally, the habit of praying has been done since the early age,therefore, parents often invite their children to perform prayers together in order to teach them a habituation. Obstacles felt by parents when they ask to pray in a congregation in the mosque, where children mostly active and rowdy,they may disrupt the concentration of other worshipers.Such places then